Development of a novel method to grow mono-/few-layered MoS2 films and MoS2-graphene hybrid films for supercapacitor applications - Patil, Sagar; Harle, Arti S.; Sathaye, Shivaram; Patil, Kashinath (CrystEngComm, 2014)
The controlled synthesis of highly crystalline MoS2 atomic layers remains a challenge for practical applications of this emerging material. We demonstrate a facile method to synthesize crystalline mono-layered/few-layered MoS2 thin films at the liquid-liquid interface which can be suitably transferred to the substrates. The films are characterized by XRD for their crystal structure and by SEM and TEM for the morphology. MoS2 nanosheet-graphene nanosheet (MoS2-GNS) hybrid films have been developed by the application of layer-by-layer (LbL) techniques. Cyclic voltammetry and other electrochemical characterization techniques reveal that the hybrid film electrode shows a specific capacitance of 282 F g(-1) at a scan rate of 20 mV s(-1). The as-obtained hybrid electrode is robust and exhibits much improved cycle life (>1000), retaining over 93% of its initial capacitance as revealed by galvanostatic charge/discharge studies. The confirmation of better performance as a supercapacitor of the composite was studied by electrochemical impedance spectroscopy. These results indicate that the MoS2-GNS hybrid is a promising candidate for the electrode material in supercapacitor applications.